In utero electroporation induces cell death and alters embryonic microglia morphology and expression signatures in the developing hypothalamus - Jessica M. Rosin (Journal of Neuroinflammation, 2018)
Abstract Background Since its inception in 2001, in utero electroporation (IUE) has been widely used by the neuroscience community. IUE is a technique developed to introduce plasmid DNA into embryonic mouse brains without permanently removing the embryos from the uterus. Given that IUE labels cells that line the ventricles, including radial fibers and migrating neuroblasts, this technique is an excellent tool for studying factors that govern neural cell fate determination and migration in the developing mouse brain. Whether IUE has an effect on microglia, the immune cells of the central nervous system (CNS), has yet to be investigated. Methods We used IUE and the pCIG2, pCIC-Ascl1, or pRFP-C-RS expression vectors to label radial glia lining the ventricles of the embryonic cortex and/or hypothalamus. Specifically, we conducted IUE at E14.5 and harvested the brains at E15.5 or E17.5. Immunohistochemistry, along with cytokine and chemokine analyses, were performed on embryonic brains with or without IUE exposure. Results IUE using the pCIG2, pCIC-Ascl1, or pRFP-C-RS vectors alone altered microglia morphology, where the majority of microglia near the ventricles were amoeboid and displayed altered expression signatures, including the upregulation of Cd45 and downregulation of P2ry12. Moreover, IUE led to increases in P2ry12− cells that were Iba1+/IgG+ double-positive in the brain parenchyma and resembled macrophages infiltrating the brain proper from the periphery. Furthermore, IUE resulted in a significant increase in cell death in the developing hypothalamus, with concomitant increases in cytokines and chemokines known to be released during pro-inflammatory states (IL-1β, IL-6, MIP-2, RANTES, MCP-1). Interestingly, the cortex was protected from elevated cell death following IUE, implying that microglia that reside in the hypothalamus might be particularly sensitive during embryonic development. Conclusions Our results suggest that IUE might have unintended consequences of activating microglia in the embryonic brain, which could have long-term effects, particularly within the hypothalamus.